Power blues ; Bucking the system ; The Eraserheads [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
The three parts viewed are : the Masinloc coal-fired power plant operation being protested by environmentalists and blocking the governments power development programs; the people in the judiciary charged of graft and corruption in 1993 are still unidentified; and an interview with the Eraserheads band members.
Power blues (16 min.) -- Bucking the system (13 min.) -- The Eraserheads (16 min.).
VHS.
Keywords: Eraserheads; Coal-fired power plants -- Philippines -- Masinloc (Zambales).; Band musicians -- Philippines; Political corruption -- Philippines